2019
DOI: 10.1002/ecy.2556
|View full text |Cite
|
Sign up to set email alerts
|

Dry conditions and disturbance promote liana seedling survival and abundance

Abstract: Species composition and community structure in Neotropical forests have been severely affected by increases in climate change and disturbance. Among the most conspicuous changes is the proliferation of lianas. These increases have affected not only the carbon storage capacity of forests but also tree dynamics by reducing tree growth and increasing mortality. Despite the importance of lianas in Neotropical forests, most of the studies on lianas have focused on adult stages, ignoring dynamics at the seedlings st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 64 publications
(170 reference statements)
3
23
0
Order By: Relevance
“…However, at the community level, we observed positive and negative ER-SIF 757 variations. We hypothesize that the variations could also be related to drought-driven ecological dynamics with potential for compelling the ERs' community demography to express a higher or lower Φ F and Ω C (e.g., the proliferation of tropical plants that increase tree mortality [27], a decrease in pollinators resulting in decreased natality of specific plant species [77], or a decrease in the fauna's floristic resources, thereby affecting the fauna composition [78,79] and leading to changes in Φ F by limiting the plants' N availability [16] from manure and urine stock flows). Nevertheless, similar to previous results [7], we found a widespread SIF 757 reduction during the El Niño 2015-2016 phenomena in which the positive and negative ER-SIF 757 variations suggest that both physiological responses and mortality may be taking place with a higher frequency in ERs with higher SIF 757 variations.…”
Section: Sif 757 Response During the El Niño 2015-2016 Extreme Droughmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the community level, we observed positive and negative ER-SIF 757 variations. We hypothesize that the variations could also be related to drought-driven ecological dynamics with potential for compelling the ERs' community demography to express a higher or lower Φ F and Ω C (e.g., the proliferation of tropical plants that increase tree mortality [27], a decrease in pollinators resulting in decreased natality of specific plant species [77], or a decrease in the fauna's floristic resources, thereby affecting the fauna composition [78,79] and leading to changes in Φ F by limiting the plants' N availability [16] from manure and urine stock flows). Nevertheless, similar to previous results [7], we found a widespread SIF 757 reduction during the El Niño 2015-2016 phenomena in which the positive and negative ER-SIF 757 variations suggest that both physiological responses and mortality may be taking place with a higher frequency in ERs with higher SIF 757 variations.…”
Section: Sif 757 Response During the El Niño 2015-2016 Extreme Droughmentioning
confidence: 99%
“…A reduced CO 2 uptake limits photosynthetic activity and results in lower SIF values. Drought can also cause mortality via carbon starvation, hydraulic failure, and phloem transport failure [23], which alter the ecological balance by shifting the composition of vegetation communities [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Lianas constitute an important component of Neotropical forests (Schnitzer and Bongers , , Umaña et al. ) and are particularly abundant in the seedling community of the LFDP (Umaña et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…) and are particularly abundant in the seedling community of the LFDP (Umaña et al. ). Although trait data for lianas are scarce, previous studies have suggested that lianas exhibit a similar range of life‐history strategies than tree species (Gilbert et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation